SANCTIONS FOR ELECTORAL PROPAGANDA IN DISAGREEMENT WITH HEALTH REGULATIONS IN THE 2020 ELECTIONS: Case Study of TSE Ruling No. 0600367-86.2020.6.05.0143 - Soares Alcântara, Adriana; de Almeida Morais, Felipe (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
ABSTRACT: This article deals with the analysis of the collegiate decision handed down by the Superior Electoral Court in the proceedings in Special Appeal No. 0600367-86.2020.6.05.0143, ratifying the decision handed down by the Regional Electoral Court of Bahia that used as a basis the precept inserted in the Magna Carta by art. 1°, § 3°, VI, of Constitutional Amendment No. 107/2020, as well as in its own Administrative Resolution No. 39/2020, which provided, in its art. 5°, §1°, for the application of the pecuniary penalty provided for in art. 36, § 3º, of Law No. 9,504/97, since, if there was processing and investigation of the acts of irregular electoral propaganda, the violation of its provisions was proven. An exploratory methodology was used with research into specific electoral case law and comparison of judgments. Once the study was concluded, it was concluded that it is possible to apply fines for non-compliance with judicial determinations in injunctive relief that determine the non-performance or suspension of propaganda acts in disagreement with health standards, as long as they are recorded in the body of judicial proceedings and applied in a reasonable and proportional manner to the gravity of the facts and conduct.